Reducing neuroendocrine psychosocial stress response through socio-emotional dyadic but not mindfulness online training - Matthaeus, Hannah; Heim, Christine; Voelkle, Manuel C.; Singer, Tania (Frontiers in Endocrinology, 2024)
Stress-related diseases pose significant health risks and show wide prevalence. Empirical evidence suggests that contemplative practices, such as socio-emotional dyadic mental exercises, hold promise in mitigating the adverse effects of stress and promoting psychosocial well-being. This study aimed to investigate the differential effects of two online contemplative mental training programs on the psychosocial stress response: the first involved classic mindfulness practices, while the second incorporated a socio-emotional dyadic approach known as Affect Dyad. The study was conducted as part of the longitudinal CovSocial project's phase 2 in the context of the COVID-19 pandemic. 140 individuals participated in the Trier Social Stress Task (TSST), where the psychosocial stress response was assessed with cortisol saliva samples and subjective stress questionnaires in a crosssectional design after the active training groups finished their intervention period. Participants were randomly assigned to the socio-emotional training group, mindfulness-based training group, or a control group that did not receive any training. Both training programs consisted of a ten-week intervention period with a daily 12-minute app-based mental training practice and weekly 2-hour online coaching sessions led by mental training teachers. Results showed that the socio-emotional Dyad group but not the mindfulness-based group exhibited significantly lower cortisol levels at 10, 20, 30, and 40 minutes after the stressor as well as lower total cortisol output compared to the control group during the TSST, indicating a reduced hormonal stress response to a social stressor. Subjective markers did not show differences between the three groups. These findings indicate that the daily socio-emotional dyadic practice, which emphasizes non-judgmental and empathic listening as well as the acceptance of challenging emotions in the presence of others within one's daily life context, may serve as a protective factor against the adverse effects of psychosocial stress triggered by the fear of negative social judgments. Given the high prevalence of stress-related diseases, such online mental training programs based on dyadic practices may thus represent an efficient and scalable approach for stress reduction.